Integração em psicoterapia cognitivo-comportamental: um ensaio para a pesquisa baseada em processos de mudança - Jager, Márcia Elisa (2023)
This doctoral thesis proposes a feasibility study based on research based on processes of change to substantiate the condition of efficacy and effectiveness of an integrative model in psychotherapy. The proposal is based on six theoretical articles. The first one characterizes the epistemological roots and the clinical practice of cognitive-behavioral psychotherapies throughout its development in “generations”, highlighting its essentially empirical scientific condition. This is to support the idea that it is necessary to identify and understand coherence in the epistemological structure and in the theoretical and practical model of cognitivebehavioral approaches in order to assess the pertinence and viability of an integration between psychotherapeutic approaches. The second theoretical article conceptualizes empirically supported psychotherapy and Practice in Evidence-Based Psychology (EPBP). Furthermore, it characterizes research in psychotherapy when the aim is to build qualified scientific knowledge to support clinical decision-making. Here, the feasibility studies proposed in this thesis were conceptually reviewed. This is to defend the idea that research, carefully planned and structured, must be carried out so that a new integrative model in cognitive-behavioral psychotherapy can be scientifically disseminated, enabling therapists to practice evidence-based. The third, fourth and fifth theoretical articles, respectively, present the conceptual model of Schema Therapy (ST) and Cognitive Narrative Therapy (CBT) and their characteristics of clinical management to defend the idea that, epistemologically, theoretically and practically, the integration between these psychotherapeutic approaches is possible. Arguing that the integration between psychotherapeutic models is recognized, scientifically and professionally, by the cognitivebehavioral approach; that the integration between the suggested psychotherapeutic models would enable an empirically sustained practice and/or a PPBE, that it is possible to integrate ET with CBT; that these approaches have epistemological, theoretical and practical assumptions that can be combined, the last theoretical article presents a proposal for a feasibility study based on research based on processes of change to substantiate the condition of efficacy and effectiveness of a model in psychotherapy that integrate the CBT with the ET. In the proposed thesis, the place of theoretical and practical diversity of cognitive-behavioral psychotherapies is assumed, as well as the relevance and pertinence of each one of them in the field of research and science in psychotherapy. Due to this recognition, it was intended to delineate “just” one more alternative that adds to the repertoire of therapists who also have diverse personalities, interests, profiles and theoretical identifications. That is, it is not intended here to defend that the suggested therapeutic proposal or the way of building scientific knowledge in psychotherapy are better than others. Rather, it is intended to build scientific knowledge consistent with what Cognitive Therapy has always advocated: epistemological, theoretical and practical integration and diversity as a primary tool for psychologists (and clinical researchers) in promoting mental health.